GAMBARAN PENGETAHUAN PENYAKIT CACINGAN (HELMINTHIASIS) PADA WALI MURID SDN 1, 2, 3, DAN 4 MULYOAGUNG, KECAMATAN DAU, KABUPATEN MALANG, JAWA TIMUR - Dhia Irfan Hanif; Moch Yunus; Rara Warih Gayatri (Universitas Negeri Malang, 2017)
Abstract: WHO (2016) said the helminthiasis is an infection of the intestinal parasites of the Nematodes are transmitted through the ground, Soil Transmitted Helminths or (STH). WHO (2016) reported more than 2 billion people are infected with helminthiasis. According to Indonesia Ministry of Health (2004), the prevalence of helminthiasis in children of the primary school in 2003 amounting to 33% increasing and in 2004 became 46,8%. Indonesia Ministry of Health (2005) presents results of survey of helminthiais in elementary school showed the prevalence of approximately 60%-80%. The purpose of this research is to know the description of the knowledge of the helminthiasis on caregivers SDN 1, 2, 3, and 4 Mulyoagung, Dau, Malang, East Java. This research uses descriptive methods (cross sectional) and quantitative approach. The population of the research was the entire caregivers SDN 1, 2, 3, and 4 Mulyoagung a number of 685 people, with samples 253 people. Research instrument using a questionnaire based on the indicator of knowledge on health. Engineering data retrieval done by giving questionnaires to caregivers through the student and teacher. Data analysis using descriptive statistical analysis to determine the score of the questionnaire and determine the level of knowledge of caregivers. The results of the research in general, the description of the knowledge of the disease intestinal worms (helminthiasis) on caregivers SDN 1, 2, 3, and 4 Mulyoagung, Kecamatan Dau, Malang, East Java was less, with an average score of respondents 45,81.Keywords: knowledge, helminthiasis, parents (caregivers)Abstrak: WHO (2016) mengatakan helminthiasis adalah infeksi cacing parasit usus dari golongan Nematoda usus yang ditularkan melalui tanah atau disebut Soil Transmitted Helminths (STH). WHO (2016) melaporkan lebih dari 2 miliar orang terinfeksi cacingan. Menurut DEPKES RI (2004), prevalensi cacingan pada anak sekolah dasar pada tahun 2003 sebesar 33% dan meningkat pada tahun 2004 menjadi 46,8%. DEPKES RI (2005) memaparkan hasil survei cacingan di sekolah dasar menunjukan prevalensi sekitar 60% - 80%. Tujuan dari penelitian ini adalah untuk mengetahui gambaran pengetahuan helminthiasis pada wali murid SDN 1, 2, 3, dan 4 Mulyoagung, Kecamatan Dau, Kabupaten Malang, Jawa Timur. Penelitian ini merupakan penelitian deskriptif dengan pendekatan cross sectional. Populasi penelitian adalah seluruh wali murid SDN 1, 2, 3, dan 4 Mulyoagung sejumlah 685 orang, dengan sampel sejumlah 253 orang. Instrumen penelitian menggunakan kuesioner untuk mengetahui pengetahuan terhadap kesehatan. Teknik pengambilan data dilakukan dengan memberikan kuesioner kepada wali murid melalui siswa dan guru. Analisis data menggunakan analisis statistik deskriptif untuk menentukan skor dari kuesioner dan menentukan tingkat pengetahuan wali murid. Hasil penelitian secara umum, gambaran pengetahuan penyakit cacingan (helminthiasis) pada wali murid SDN 1, 2, 3, dan 4 Mulyoagung, Kecamatan Dau, Kabupaten Malang, Jawa Timur adalah kurang, dengan skor rata-rata responden 45,81.Kata kunci: pengetahuan, cacingan (helminthiasis), wali murid